A Development Web Application for Planning Cultivate Vegetable to Maximize Profits on Nam Kam District, That Phanom, Nakhon Phanom Province, Thailand - Sirilamduan, Chadrudee; Chuaychuny, Suppakrit; Ruamboon , Kitchanut; Srisuk, Sanan (International Journal of Multidisciplinary in Management and Tourism, 2021)
In this paper, the mathematical model is proposed to optimize the vegetable cropping pattern in Nam Kam District, That Phanom, Nakhon Phanom Province, Thailand. The results showed the potential of the model to optimize vegetable cropping patterns and estimated profit of about 10,327.36 $US. (327,219 THB) with celery and coriander. A web application for vegetable crop selection and planning has also been developed for easy access enabling the farmers to utilize via mobile phone. A web application offers the cropping pattern similar to computing mathematical model technique.